Cognitive impairment in young and middle-aged patients - E. G. Demianovskaya; A. S. Vasilev; V. I. Shmyrev (Лечащий Врач, 2023)
In routine practice, neurologists and doctors of related specialties often have to deal with complaints of cognitive impairment in young and middle-aged patients, such as deterioration of memory and performance, decreased concentration, increased distraction, difficulties in learning and acquiring new professional skills. Such complaints in people of working age require special attention, differential diagnosis, identification of the root causes of such complaints. In order to objectify the presence and clarify the nature of the cognitive defect, all patients with cognitive complaints, in addition to assessing the neurological status, need to conduct a neuropsychological study with an assessment of the emotional and behavioral sphere. At the international arena, modifiable factors of cognitive impairment have been identified for people aged 45 to 60 years, among which there is arterial hypertension. Recommendations for maintaining cognitive health are formulated in order to prevent the deepening of cognitive defect. Medicamentous therapy of cognitive disorders of varying severity remains a subject for discussion, the accumulation of evidence continues. A number of experts believe that at the stage of mild and moderate cognitive disorders, it is advisable to influence the glutamatergic, noradrenergic, dopaminergic neurotransmitter systems. The expediency of prescribing a combination of vascular and nootropic active substances, including as part of combined preparations, is indicated. Such medications include the drug, containing an extract of the leaves of ginkgo biloba and nicotinoyl gamma-aminobutyric acid. For each of these components, there is a pathogenetic justification for efficacy in mild and moderate cognitive disorders. The efficacy of the drug in cognitive deficits in patients, including middle-aged, was confirmed in a multicenter randomized open comparative study of the clinical efficacy and safety of the drug in patients with cognitive impairment and chronic cerebral ischemia, which was conducted in 5 clinical centers located in Russia. In patients with vascular cognitive impairment, including middle-aged, an increase in scores on neurocognitive scales was shown against the background of the use of the combined drug, significantly superior to monotherapy with a drug based on ginkgo biloba. The positive dynamics was especially significant in patients with arterial hypertension. The authors of the study concluded that the combined drug is an effective and promising tool for the treatment of cognitive impairment in patients with chronic cerebral ischemia, including the middle age category.